2006
DOI: 10.1186/1465-9921-7-113
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that CFTR is expressed in rat tracheal smooth muscle cells and contributes to bronchodilation

Abstract: Background: The airway functions are profoundly affected in many diseases including asthma, chronic obstructive pulmonary disease (COPD) and cystic fibrosis (CF). CF the most common lethal autosomal recessive genetic disease is caused by mutations of the CFTR gene, which normally encodes a multifunctional and integral membrane protein, the CF transmembrane conductance regulator (CFTR) expressed in airway epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 40 publications
3
64
1
1
Order By: Relevance
“…The CFTR is insensitive to DIDS [23], and this result was confirmed in the present study, suggesting that the channel observed in rat IPA may be similar to that observed in bovine pulmonary arterial smooth muscle [17]. The pharmacological profile of CFTR activation in IPA using MPB activators (MPB-91.MPB-07.MPB-80) studied with the iodide efflux and isometric tension techniques (in the present report) is similar to that previously obtained in rat or mouse aortic myocytes [6,7], epithelial cells [21] and tracheal myocytes [5]. Moreover, endothelium removal did not influence pulmonary arterial vasorelaxation in response to MPBs, a result in agreement with that previously reported for rat and mouse aorta [6,7].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The CFTR is insensitive to DIDS [23], and this result was confirmed in the present study, suggesting that the channel observed in rat IPA may be similar to that observed in bovine pulmonary arterial smooth muscle [17]. The pharmacological profile of CFTR activation in IPA using MPB activators (MPB-91.MPB-07.MPB-80) studied with the iodide efflux and isometric tension techniques (in the present report) is similar to that previously obtained in rat or mouse aortic myocytes [6,7], epithelial cells [21] and tracheal myocytes [5]. Moreover, endothelium removal did not influence pulmonary arterial vasorelaxation in response to MPBs, a result in agreement with that previously reported for rat and mouse aorta [6,7].…”
Section: Discussionsupporting
confidence: 78%
“…The CFTR was generally regarded as specifically expressed in epithelial cells until evidence for CFTR expression in nonepithelial tissues emerged. CFTR is expressed in cardiac muscle cells [2], brain [3] and endothelia [4], and has recently been found in tracheal smooth muscle cells (SMCs) [5] and aortic SMCs of rats and mice [6,7]. Despite this CFTR expression profile, the clinical picture of patients suffering from the CFTR-related disease cystic fibrosis appears to be unrelated to cardiac, vascular and brain dysfunction.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The ex situ organ-bath technique is commonly used to determine vasomotor function of isolated blood vessels (23)(24)(25). In the present work, first and second divisions of the renal artery were dissected and cut into 3-mm-long rings.…”
Section: Ex Situ Vascular Function Studymentioning
confidence: 99%